1991
DOI: 10.4139/sfj.42.729
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Behavior of Electroless Gold Plating with Ascorbic Acid as a Reducing Agent.

Abstract: A novel electroless (autocatalytic) gold plating bath containing sodium L-ascorbate as the reducing agent has been developed. A suitable bath composition was formulated based on the results of an electrochemical study in which were determined at a gold electrode the anodic polarization curves of various reducing agents and the cathodic polarization curves of sodium tetrachloroaurate (III) dissolved in solutions of sodium sulfite and/or sodium thiosulfate. A typical bath containing 0.0125mol /dm3 sodium tetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 1 publication
1
19
0
Order By: Relevance
“…The following stabilizing agents are reported to be effective: 1,2-diaminoethane with KBr (30-33), ethylenediamine (34,35), ethylenediamine tetraacetic acid (EDTA) (30-33), triethanolamine (36), nitrilotriacetic acid (36), and sodium thiosulfate (36). Using ascorbic acid as the reducing agent, Kato et al (37,38) showed that the Au(I) sulfite complex can be reduced to gold autocatalytically, but the deposition rate was very low. They found that the deposition rate can be increased greatly by adding thiosulfate as the second complexing agent.…”
Section: Sulfite Bathsmentioning
confidence: 99%
“…The following stabilizing agents are reported to be effective: 1,2-diaminoethane with KBr (30-33), ethylenediamine (34,35), ethylenediamine tetraacetic acid (EDTA) (30-33), triethanolamine (36), nitrilotriacetic acid (36), and sodium thiosulfate (36). Using ascorbic acid as the reducing agent, Kato et al (37,38) showed that the Au(I) sulfite complex can be reduced to gold autocatalytically, but the deposition rate was very low. They found that the deposition rate can be increased greatly by adding thiosulfate as the second complexing agent.…”
Section: Sulfite Bathsmentioning
confidence: 99%
“…We selected this system in view of the fact that it is used successfully for formulating noncyanide, autocatalytic electroless gold plating baths yielding good bath stability and deposit properties [10][11][12].…”
Section: Non-cyanide Thiosulfate-sulfite Bath For Electroplating Softmentioning
confidence: 99%
“…The composition and operating conditions of the noncyanide SCEL bath are listed in Table 3, which are similar to those of the autocatalytic bath containing the same ligands [10] except that the reducing agent (ascorbic acid) was excluded. For bath makeup, the commonly available trivalent gold salt, NaAuCl 4 , is used, but the Au(III) in this salt is reduced immediately to Au(I) upon addition of Na 2 SO 3 , forming Au(I) sulfite complex.…”
Section: Non-cyanide Bathmentioning
confidence: 99%
“…The thiourea bath was developed and subsequently improved by a group of investigators at Hitachi, Ltd. (17,25). Basic and improved versions of the bath composition and operating conditions are shown in Table 2.…”
Section: Thiourea Bathmentioning
confidence: 99%
“…In view of the prior successful development of electroless gold plating baths containing both thiosulfate and sulfite (17,18), which will be described in the subsequent section, the present authors and collaborators investigated the possibility of electroplating soft gold from a bath containing the two ligands (19). It was found that the mixed ligand bath is highly stable even without the addition of any stabilizer.…”
mentioning
confidence: 99%